Imprisonment in Crime Control Efforts - Dian Mustika Intan; E. Soponyono (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
Crime prevention in Indonesia is often related to criminal enforcement through the prison system, which is one of the criminal sanctions that are often used as a means of crime prevention in various categories. The study used normative juridical research by performing library studies of legal and literary materials associated with the object of the study. The purpose of this study is to determine the effectiveness of prison penal penalties in criminal policy as well as problems in the implementation of imprisonment at the penitentiary. The results of the study conclude that the effectiveness of imprisonment will be reviewed from two main aspects of the purpose of punishment, namely, first, the aspect of society's protection, which is very specific to society. Second, it is seen from the aspect of the improvement of the individual who focuses on improving the behavior of the perpetrators. Problems are often encountered in prison criminal executions at suchpenitentiary: overcrowding inpenitentiary, the rise of new crimes in the penitentiary, the differences in correctional facilities, not fulfilling the basic rights of prisoners, a lack of integrity and guidance for the guards